Exploring the experiences of older adults living with asthma in the United Kingdom: A co-produced qualitative study - Tracy Jackson; Flora Flinn; Lewis Rafferty; Elisabeth Ehrlich; Monica Fletcher (Aging and Health Research, 2022)
Background: Older adults are the fastest growing population in the UK, but asthma is often underdiagnosed, undertreated and poorly self-managed in this population. It is necessary to explore the experiences of older adults with asthma to identify areas of research that could improve quality of life. This study aimed to explore the perceptions of older adults in the UK living with asthma and how it impacts their lives. Methods: Telephone interviews were conducted with 15 adults with General Practitioner diagnosed asthma, aged 60 years and over, from across the UK. Interviews were audio-recorded, transcribed verbatim and thematically analysed. This study was co-produced with an Asthma UK Centre for Applied Research (AUKCAR) Patient and Public Involvement Lead and guided by the National Institute for Health Research UK standards for Public Involvement in Research to ensure meaningful public involvement. Results: Themes clustered around impact of asthma, managing asthma, interaction with healthcare and understanding of asthma. Participants experienced increased physical, psychological and social impacts of asthma management as they aged which led to feelings of isolation. Competing multimorbidities and polypharmacy complicate treatment and self-management of asthma. Ageism and a lack of empathy from health care providers were mentioned by the majority participants. Quality of care varied widely across the UK, however all participants had seen a healthcare professional for an asthma review in the previous 12 months. Conclusions: Older adults experience increased challenges in managing their asthma due to increased multimorbidities, polypharmacy and ageism from healthcare providers.